THE UTILIZATION OF THE VOA PODCAST FOR EFL’S RESPONSE TASKS OF LISTENING ACTIVITY AT MAN 3 NGAWI - Fachriza, Aries (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
Voice of America (VoA) Podcast is one of the media for English learning that broadcasts various information with an American accent. This provides a wide range of materials video and audio to train response task skills in listening activities. This study aims to determine the achievement of EFL at the secondary level at MAN 3 Ngawi in listening to response tasks through VOA podcasts. This study employs quantitative with a quasi-experiment design. It utilizes a pretest-posttest as the technique of collecting data and an independent sample T-Test as the data analysis. This study showed that the utilization of VOA podcasts on response tasks is proven effective for students’ listening. It revealed that the value of statistical data (significance value) was 0.000 (Less than 5 %). It means that the VOA podcast contributes to increase students’ response tasks in listening material. It also drives students’ enthusiasm and activeness in the learning process to attain good learning outcomes. On the other hand, the teachers can choose and determine various suitable and interesting learning alternatives.